Post-COVID Consumer Behavior Shifts in the Online Food Delivery Service Sector in Malaysia - Teow Boon Keong; Yee Jing Foo; Meenu Baliyan; Yip Chi Fong; Yeap Yong Ying; Yap Si Ning; Vaishnavi V; Ye Zuo Tai; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
The COVID-19 pandemic has accelerated the adoption of digital services, particularly online food delivery platforms, leading to notable changes in consumer behavior. This study aims to examine post-COVID shifts in consumer behavior in the food delivery sector by focusing on GrabFood users in Malaysia and to identify the key factors driving these changes. A quantitative approach was used, collecting survey data from 150 users and applying multiple regression analysis to examine the effects of health and safety concerns, convenience, price sensitivity and promotion, ease of use, and service quality on post-pandemic consumer behavior. The results indicate a significant increase in both usage frequency and spending on GrabFood after the pandemic. Price sensitivity and promotion exert the strongest influence on consumer behavior (? = 0.424, p 0.001), followed by health and safety concerns (? = 0.418, p 0.001) and perceived convenience (? = 0.217, p 0.01). In contrast, perceived ease of use and enhanced service quality show weaker yet significant effects. The findings suggest that consumer behavior changes initiated during the pandemic have become enduring patterns. Practically, the study provides insights for platform operators to prioritize competitive pricing, promotional strategies, and safety assurance to sustain user engagement and loyalty.